Sexual issues resources for strategic pastoral counseling - Wahking, Harold L.; Zimmerman, Gene (Grand Rapids, MI Baker, 1994)
Includes bibliographical references.
Keywords: Pastoral counseling; Sex counseling; Sex -- religious aspects -- Christianity